The Effect of Entrepreneurship Education, Commitment to Entrepreneurship on Nascent Halalpreneurial Intention of Muslim Students in Surabaya - Rika Rika; Ririn Tri Ratnasari (Universitas Airlangga, 2022)
ABSTRAK Entrepreneurship education dianggap mempunyai pengaruh terhadap nascent halalpreneurial intention. Penelitian ini menggunakan mahasiswa Muslim di Indonesia yang sedang atau telah menempuh mata kuliah kewirausahaan sebagai obyek penelitian. Selain itu, entrepreneurship education dapat menjadi faktor penting timbulnya commitment to entrepreneurship pada mahasiswa dan menumbuhkan niat berbisnis dikalangan mahasiswa. Hal ini karena entrepreneurship diakui sebagai cara untuk menciptakan lapangan kerja dan mengurangi pengangguran. Menggunakan metode penelitian kuantitatif dan kuesioner yang disebarkan secara online kepada responden mahasiswa Muslim, ditemukan bahwa entrepreneurship education dan commitment to entrepreneurship berkaitan dengan nascent halalpreneurial intention pada mahasiswa Muslim di Surabaya. Kata Kunci: Entrepreneurship, Entrepreneurship education, Commitment to entrepreneurship, Innovativeness, Nascent halalpreneurial intention. ABSTRACT Entrepreneurship education is considered to have an influence on nascent halalpreneurial intention. This study uses Muslim students in Indonesia who are currently taking or have taken entrepreneurship courses as research objects. In addition, entrepreneurship education can be an important factor in generating commitment to entrepreneurship among students and fostering business intentions among students. This is because entrepreneurship is recognized as a way to create jobs and reduce unemployment. Using quantitative research methods and questionnaires distributed online to Muslim student respondents, it was found that entrepreneurship education and commitment to entrepreneurship were related to nascent halalpreneurial intention to Muslim students in Surabaya. Keywords: Entrepreneurship, Entrepreneurship education, Commitment to entrepreneurship, Innovativeness, Nascent halalpreneurial intention. DAFTAR PUSTAKA Adam, A., & Fayolle, A. (2015). Bridging the entrepreneurial intention-behaviour gap: The role of commitment and implementation intention. International Journal of Entrepreneurship and Small Business, 25(1), 36-54. Alam, M. Z., Kousar, S., Rehman, C. A. (2019). Role of entrepreneurial motivation on entrepreneurial intentions and behaviour: Theory of planned behaviour extension on engineering students in Pakistan. Journal of Global Entrepreneurship Research, 9(10), 1-20. Ayalew, M. M. (2020). Bayesian hierarchical analyses for entrepreneurial intention of students. Journal of Big Data, 7(1), 1–23. https://doi.org/10.1186/s40537-020-00293-x. Badan Pusat Statistik. (2020). Tingkat pengangguran terbuka (TPT) sebesar 7,07 persen. Retrieved from https://www.bps.go.id/pressrelease/2020/11/05/1673/agustus-2020–tingkat-pengangguran-terbuka–tpt–sebesar-7-07-persen.html. Baliamoune-Lutz, M., & Garello, P. (2015). The effect of tax progressivity on the quality of entrepreneurship: How significant is the phenomenon of “poor entrepreneurship”?. SSRN Electronic Journal. http://dx.doi.org/10.2139/ssrn.2585567 Bosma, N., Schott, T., Terjesen, S., & Kew, P. (2016). Global Entrepreneurship Monitor 2015 to 2016: Special topic report on social entrepreneurship. http://dx.doi.org/10.2139/ssrn.2786949]. Bosma, N., & Kelley, D. (2019). Global entrepreneurship monitor 2018/2019 global report. Chile: Gráfica Andes. Bustamam, U. S. A. (2012). Growth strategy of Malay entrepreneurs – challenges and opportunities: A Malaysian. Malaysia: Universiti Sains Islam Malaysia. Gollwitzer, P. M., & Brandstätter, V. (1997). Implementation intentions and effective goal pursuit. Journal of Personality and Social Psychology, 73(1): 186–199. http://dx.doi.org/10.1037/0022-3514.73.1.186 Hamdi, A. S. & Bahruddin, E. (2014). Metode penelitian kuantitatif aplikasi dalam pendidikan. Yogyakarta: Deepublish. Haryono, S. (2016). Metode SEM untuk penelitian manajemen dengan AMOS LISREL PLS. Bekasi: Badan Penerbit PT. Intermedia Personalia Utama. Hassan, A., Saleem, I., Anwar, I., & Hussain, S. A. (2020). The entrepreneurial intention of Indian university students: The role of opportunity recognition and entrepreneurship education. Education & Training, 62(7/8), 843-861. https://doi. org/10.1108/ET-02-2020-0033 Hejazinia, R. (2015). The impact of IT-based entrepreneurship education on entrepreneurial intention. International Journal of Management, Accounting and Economics, 2(3), 243–253. Linan, F. (2004). Intention-based models of entrepreneurship education. Piccolla Impresa/Small Business, 3(1), 11–35. Hussain, A., & Norashidah, D. (2015). Impact of entrepreneurial education on entrepreneurial intentions of Pakistani students. Journal of Entrepreneurship and Business Innovation, 2(1), 43. http://dx.doi.org/10.5296/jebi.v2i1.7534 Enggartiasto tingkat kewirausahaan di indonesia rendah. (2018). https://republika.co.id/berita/ekonomi/korporasi/18/10/18/pgsax3383enggartiasto-tingkat kewirausahaan-di-indonesia-rendah Jena, R. K. (2020). Measuring the impact of business management Student’s attitude towards entrepreneurship education on entrepreneurial intention: A case study. Computers in Human Behavior, 107(December 2018), 106275. https://doi.org/10.1016/j.chb.2020.106275 Kementerian Agama Republik Indonesia. (2017). Terjemahan Al-Qur’an. Jakarta: Kemenag RI. Kibler, E. (2012). Formation of entrepreneurial intentions in a regional context. Entrepreneurship & Regional Development, 25(3-4), 293-323. https://doi.org/10.1080/08985626.2012.721008 Koyviriyakul, K. (2016). The intention of software developers to be startup entrepreneurs. Unpublished master thesis, Bangkok: Thammasart University. Kurniawan, R. (2013). Pengaruh penerapan model pembelajaran teaching factory 6 langkah (TF-6M) dan prestasi belajar kewirausahaan terhadap minat wirausaha. Jurnal Pendidikan Teknologi Kejuruan, 10(1), 57-66. https://doi.org/10.17509/invotec.v10i1.5092 Linan, F., & Chen, Y. W. (2009). Development and cross‐cultural application of a specific instrument to measure entrepreneurial intentions. Entrepreneurship Theory and Practice, 33(3), 593- 617. https://doi.org/10.1111/j.1540-6520.2009.00318.x Margharita, B., Panagiotis, K., Yves, P., & Lieve, V. (2016). EnterComp: The entrepreneurship competence framework. Luxembourg: Publications Office of the European Union. http://dx.doi.org/10.2791/160811 Meyer, J. P., & Herscovitch, L. (2001). Commitment in the workplace: Toward a general model. Human Resource Management Review, 11(3), 299–326. https://doi.org/10.1016/S1053-4822(00)00053-X Munawaroh. (2018). The effect of problem-based learning (PBL) method on students critical thinking skills on entrepreneurship practice course (a study on economics education department in the college education and teachers' training PGRI Jombang East Java Indonesia). Journal of Entrepreneurship Education, 21(1). Nabi, G., Liñan, F., Fayolle, A., Krueger, N., & Walmsley, A. (2017). The impact of entrepreneurship education in higher education: A systematic review and research agenda. Academy of Management Learning and Education, 16(2), 277–299. https://doi.org/10.5465/amle.2015.0026 Nowiński, W., Haddoud, M. Y., Lančarič, D., Egerová, D., & Czeglédi, C. (2019). The impact of entrepreneurship education, entrepreneurial self-efficacy and gender on entrepreneurial intentions of university students in the Visegrad countries. Studies in Higher Education, 44(2), 361–379. https://doi.org/10.1080/03075079.2017.1365359. Pittaway, L., & Cope, J. (2016). Entrepreneurship education: a systematic review of the evidence. International Small Business Journal 25(5), 479-510. http://dx.doi.org/10.1177/0266242607080656 Ratnasari, R. T. (2020). Halal tourism based on value creation. Al-Uqud : Journal of Islamic Economics, 4(2), 268-284. https://doi.org/10.26740/al-uqud.v4n2.p268-284 Ratnasari, R. T., Gunawan, S., Possumah, B. T., Widiastuti, T., & Herianingrum, S. (2019). Halal food certification for improving the competitiveness of small and medium enterprises, Opcion, 35(22), 510-525. http://dx.doi.org/10.18502/kss.v3i13.4266 Ratnasari, R. T., Ula, U. F., & Sukmana, R. (2020). Can store image moderate the influence of religiosity level on shopping orientation and customers’ behavior in Indonesia?. Journal of Islamic Accounting and Business Research, 12(1), 78-96. https://doi.org/10.1108/JIABR-01-2017-0006 Rasli, A. M., Khan, S.U., Malekifar, S., & Jabeen, S. (2013). Factors affecting entrepreneurial intention among graduate students of Universiti Teknologi Malaysia. International Journal of Business and Social Science, 4(2), 182-188. Ruskovaara, E., & Pihkala, T. (2015). Entrepreneurship education in schools: Empirical evidence on the teacher’s role. The Journal of Educational Research, 108(3), 236–249. https://doi.org/10.1080/00220671.2013.878301 Sherkat, A., & Chenari, A. (2020). Assessing the effectiveness of entrepreneurship education in the universities of Tehran province based on an entrepreneurial intention model. Studies in Higher Education, 0(0), 1–19. https://doi.org/10.1080/03075079.2020.1732906 Souitaris, V., Zerbinati, S., & Al-Laham, A. (2007). Do entrepreneurship programmes raise entrepreneurial intention of science and engineering students? The effect of learning, inspiration and resources. Journal of Business Venturing, 22(4), 566–591. https://doi.org/10.1016/j.jbusvent.2006.05.002 Thompson, E. K. (2009). Individual entrepreneurial intent: Construct clarification and development of an internationally reliable metric. Entrepreneurship Theory and Practice, 33(3), 669–694. https://doi.org/10.1111/j.1540-6520.2009.00321.x. Tuazon, G., Bellavitis, C., & Filatotchev, I. (2018). Nascent entrepreneurship research: Theoretical challenges and opportunities. Academy of Management Proceedings, 1–49. https://doi.org/10.5465/AMBPP.2018.11583abstract Ucbasaran, D., Westhead, P., & Wright, M. (2000). The focus of entrepreneurial research: Contextual and process issues. Entrepreneurship: Theory and Practice, 25(4), http://dx.doi.org/10.1177/104225870102500405 Utami, W. C. (2017). Attitude, subjective norms, perceived behavior, entrepreneurship education and self-efficacy toward entrepreneurial intention university student in Indonesia. European Research Studies Journal, 20(2), 475-495. Vamvaka, V., Stoforos, C., Palaskas, T., & Botsaris, C. (2020). Attitude toward entrepreneurship, perceived behavioral control, and entrepreneurial intention: dimensionality, structural relationships, and gender differences. Journal of Innovation and Entrepreneurship, 9(1). https://doi.org/10.1186/s13731-020-0112-0 Verhaest, D., & Baert, S. (2018). The effects of workplace learning in higher education on employment and match quality: Is there an early career trade-off? Empirical Economics, 55(3),1229–1270. 10.1007/s00181-017-1308-4 Wals, A. E. (2009). The UNESCO: Review of contexts and structures for education for sustainable development. Paris, France: UNESCO. Wathanakom, N., Khlaisang, J., & Songkram, N. (2020). The study of the causal relationship between innovativeness and entrepreneurial intention among undergraduate students. Journal of Innovation and Entrepreneurship, 9(1). https://doi.org/10.1186/s13731-020-00125-5 Wei, X., Liu, X., & Sha, J. (2019). How does the entrepreneurship education influence the students’ innovation? Testing on the multiple mediation model. Frontiers in Psychology, 10(July). https://doi.org/10.3389/fpsyg.2019.01557 Welsch, H., Liao, J., Pistrui, D., Oksöy, D., & Huang, W. (2003). Entrepreneurial commitment, sacrifice, motivations and growth aspirations of Chinese entrepreneurs. Retrieved from http://citeseerx.ist.psu.edu/viewdoc/download?doi=10.1.1.336.6730&rep=rep1&type=pdf Xu, X., Ni, H., & Ye, Y. (2016). Factors influencing entrepreneurial intentions of Chinese secondary school students: An empirical study. Asia Pacific Education Review, 17, 625-635. https://doi.org/10.1007/s12564-016-9439-4